GEOPOLITICAL LANDMARKS: CENTRAL ASIA TODAY - LAUMULIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2008)
The year 2007 was a time of geopolitical changes for the region, some of which remained latent but completely analyzable. The geoeconomic factors and the worldwide financial crisis (a crisis of liquidity and defaults as well as instability in the international financial markets), the rising prices for basic commodities such as energy resources and foodstuffs, the economic growth in Russia, China, and India, and the rising importance of the energy security issue, etc. inevitably affected the situation in Central Asia. The 2007-2008 crisis began in the mortgage system of the United States and spread like wildfire to the global banking and financial systems. It caused an economic decline in the United States and, by the end of 2007, reached the euro zone. Depreciation of the world’s main currency has hit the global economy; the value of dollar savings is steadily decreasing while export incomes converted into national currencies are losing their value. Transborder investment projects are at risk. Strange as it may seem the states with currencies that could run the risk of gaining value have the largest dollar reserves. This fully applies to the tenge of Kazakhstan. Today, there is the danger of an uncontrollable and highly uncertain situation developing in the global economy that could continue for a long time to come. Countries and regions are exposed to considerable cumulative effects in the political or even military-political spheres. What is going on in the world today may hit the Kazakhstani economy either in the financial or the real sector: a financial shock spreads faster than a shock in the consumer sphere, which politicians should also take into account. The United States is steadily losing control over its own national currency; it is no longer able to keep down inflation without raising the interest rate. The latter invites liquidity but interferes with economic growth. Translated into terms of the global financial order, this means that the dollar is on the verge of losing its anchor currency status. This may happen much earlier than expected. The rest of the world will be hit: the universal currency served all and helped maintain international stability.